Response-based selection of barley cultivars and legume species for complementarity: Root morphology and exudation in relation to nutrient source. (February 2017) - Giles, Courtney D.; Brown, Lawrie K.; Adu, Michael O.; Mezeli, Malika M.; Sandral, Graeme A.; Simpson, Richard J.; Wendler, Renate; Shand, Charles A.; Menezes-Blackburn, Daniel; Darch, Tegan; Stutter, Marc I.; Lumsdon, David G.; et al.
Highlights: Phenotypic response to nutrient source in barley cultivars and legume species. Divergent responses based on root morphology and exudation. Potential plant combinations for improved nutrient acquisition identified. Abstract: Phosphorus (P) and nitrogen (N) use efficiency may be improved through increased biodiversity in agroecosystems. Phenotypic variation in plants' response to nutrient deficiency may influence positive complementarity in intercropping systems. A multicomponent screening approach was used to assess the influence of P supply and N source on the phenotypic plasticity of nutrient foraging traits in barley ( H. vulgare L.) and legume species. Root morphology and exudation were determined in six plant nutrient treatments. A clear divergence in the response of barley and legumes to the nutrient treatments was observed. Root morphology varied most among legumes, whereas exudate citrate and phytase activity were most variable in barley. Changes in root morphology were minimized in plants provided with ammonium in comparison to nitrate but increased under P deficiency. Exudate phytase activity and pH varied with legume species, whereas citrate efflux, specific root length, and root diameter lengths were more variable among barley cultivars. Three legume species and four barley cultivars were identified as the most responsive to P deficiency and the most contrasting of the cultivars and species tested. Phenotypic response to nutrient availability may be a promising approach for the selection of plant combinations for minimal input cropping systems.